1997
DOI: 10.1161/01.res.81.5.656
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia Inhibitory Factor, a Potent Cardiac Hypertrophic Cytokine, Activates the JAK/STAT Pathway in Rat Cardiomyocytes

Abstract: Leukemia inhibitory factor (LIF) is a member of the interleukin-6 family of cytokines, which induces a wide range of responses in a variety of cells. The aim of this study was to investigate whether LIF induces cardiomyocyte hypertrophy and transmits signals through the JAK/STAT (indicating just another kinase/signal transducer and activator of transcription) pathway in primary cultured neonatal rat cardiomyocytes. LIF increased protein content and [3H]phenylalanine uptake in cardiomyocytes in a dose-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(103 citation statements)
references
References 55 publications
5
98
0
Order By: Relevance
“…Moreover, activation of the gp130 receptor has been reported to induce cardiac myocyte hypertrophy both in vivo and in vitro (10,37). Further reports have shown that the JAK-STAT pathway, especially the STAT3-mediated pathway, appears to be essential in the induction of cardiac myocyte hypertrophy through gp130 (13,14). This study is the first to demonstrate that CT-1, which acts through a gp130/leukemia inhibitory factor receptor heterodimer, has the ability to induce ASM hypertrophy in the tissue milieu and that the hypertrophy is associated with increased deposition of extracellular matrix, findings consistent with our studies in severe asthma (3).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, activation of the gp130 receptor has been reported to induce cardiac myocyte hypertrophy both in vivo and in vitro (10,37). Further reports have shown that the JAK-STAT pathway, especially the STAT3-mediated pathway, appears to be essential in the induction of cardiac myocyte hypertrophy through gp130 (13,14). This study is the first to demonstrate that CT-1, which acts through a gp130/leukemia inhibitory factor receptor heterodimer, has the ability to induce ASM hypertrophy in the tissue milieu and that the hypertrophy is associated with increased deposition of extracellular matrix, findings consistent with our studies in severe asthma (3).…”
Section: Discussionmentioning
confidence: 99%
“…12 Notably, in addition to STAT3 dimers, STAT1 and STAT3 heterodimers also exist and may possess transcriptional potential that differs from the potential of STAT1 or STAT3. 9,22,23 Additionally, the DNA-binding fold contains several b-sheets that are folded similarly to the sheets found in the DNA-binding domains of NFKB1 and TP53, which suggests that numerous crosstalk possibilities exist among these 3 important stress responsive pathways. For example, NFKB1 is activated through endoplasmic reticulum stress signals in starved cancer cells, resulting in the induction of IL6.…”
Section: The Structure and Subcellular Localization Of Stat3mentioning
confidence: 99%
“…LIF stimulation increases cardiomyocyte growth and promotes a fetal gene expression pattern (upregulated c-fos, β-MHC and ANF) [77,92]. Characteristically, LIF induces myocardial hypertrophy with a predominant increase in myocardial cell length by addition of new sarcomeric units in series without concomitant increase in cell width, clearly distinguishing it from alpha-adrenergic hypertrophic responses mediated by G protein coupled receptors [75,163].…”
Section: Leukemia Inhibitory Factor and Its Potential Role In The Heartmentioning
confidence: 99%